New insights into receptor-like protein functions in Arabidopsis. (2nd July 2016) - Lv, Yanting; Yang, Nan; Wu, Jinbin; Liu, Zhijun; Pan, Lixia; Lv, Shuo; Wang, Guodong
ABSTRACT: Receptor-like proteins (RLPs) are implicated in plant development and immunity. Genome-wide sequence analysis identified fifty-seven RLPs in Arabidopsis. However, only a few AtRLPs have been functionally characterized. The major problems in determing the biological roles for AtRLP genes are the lack of suitable screening conditions and the high-degree of functional redundancy. In order to unravel the functions of AtRLP genes, recently we undertook a systematically functional analysis of AtRLP genes using transcriptional profiling and overexpression. Our findings indicate that most AtRLP genes are differentially expressed upon various conditions, and the expression of single AtRLP gene is often perturbed by multiple stimuli. Transgenic Arabidopsis plants overexpressing AtRLP genes were generated. Our study presents an overview of biological processes in which AtRLP genes possibly are involved, and provides a valuable resource for further investigations into the biological roles of AtRLP genes. In this article, we elaborate our findings and propose further strategies concerning the function of unknown AtRLP genes.